Características de utilización del imipenem/cilastatina en pacientes hospitalizados en el Hospital Nacional Almanzor Aguinaga Asenjo (HNAAA), durante los meses setiembre 2007 – febrero 2008 - Paredes Carranza, José Celso (2008)
This work was a retrospective descriptive study of cross court, where he wanted to know Characteristics of use of imipenem / cilastatin in hospitalized patients at the National Hospital Almanzor Aguinaga Asenjo (HNAAA) during September 2007 - February 2008. The study population was comprised of 1280 patients of services: Internal Medicine, Intensive Care Unit, Geriatric, Neurology, Cardiology, Pediatrics, Hematology, Gastroenterology, Oncology, Neurosurgery and Pneumology, where patients treated with imipenem / cilastatin were 161. The results were: The prevalence of use of imipenem / cilastatin was 12.5, pathologies in connection with use of imipenem / cilastatin were: septicemia45.96%, nosocomial ITU 27.33%, nosocomial pneumonia 10.57% and peritonitis 8.07%, the proportion of imipenem / cilastatin prescribed with a therapeutic purpose was 100% and prophylactic was 0%, the proportion imipenem / cilastatin prescribed based clinic was 48.45% and based microbiological was 51.55%, consumption of imipenem / cilastatin expressed in DDD/100 bed-day was 3.28, the average cost generated by the use of imipenem / cilastatin was S /. 17787.59. Also the cost generated for the month of February with a total of S /. 24605.44 and lower costs generated for the month of November with S /. 11013.13 and the trend of consumption of imipenem / cilastatin, tends to rise (positive).